2020
DOI: 10.1103/physrevlett.124.077601
|View full text |Cite
|
Sign up to set email alerts
|

Biexciton Condensation in Electron-Hole-Doped Hubbard Bilayers: A Sign-Problem-Free Quantum Monte Carlo Study

Abstract: The bilayer Hubbard model with electron-hole doping is an ideal platform to study excitonic orders due to suppressed recombination via spatial separation of electrons and holes. However, suffering from the sign problem, previous quantum Monte Carlo studies could not arrive at an unequivocal conclusion regarding the presence of phases with clear signatures of excitonic condensation in bilayer Hubbard models. Here, we develop a determinant quantum Monte Carlo (DQMC) algorithm for the bilayer Hubbard model that i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…However, in the absence of J, each layer furthermore remains individually invariant under spin rotations. Hence, the resulting excitonic condensate would need to break both U (1) charge and SU (2) × SU (2) spin rotation symmetry, precluding a finite-temperature phase transition in two dimensions, and favoring instead a Kosterlitz-Thouless transition to an exotic bi-excitonic condensate [30] at finite ∆.…”
Section: A Two-orbital Hubbard-kanamori Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the absence of J, each layer furthermore remains individually invariant under spin rotations. Hence, the resulting excitonic condensate would need to break both U (1) charge and SU (2) × SU (2) spin rotation symmetry, precluding a finite-temperature phase transition in two dimensions, and favoring instead a Kosterlitz-Thouless transition to an exotic bi-excitonic condensate [30] at finite ∆.…”
Section: A Two-orbital Hubbard-kanamori Modelmentioning
confidence: 99%
“…The density interaction term can be decomposed as in Ref. [30]. Notice that N = nA↑ + nA↓ + nB↑ + nB↓ − 2 and M = nA↑ + nA↓ − nB↑ − nB↓ both take values in {0, ±1, ±2}, and the following relation holds for x = 0, ±1, ±2:…”
Section: Sign-free Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that biexcitons play a key role for the formation of quantum droplet in photo-excited semiconductors [38]. Moreover, the biexciton condensation has been found in an electronhole Hubbard model at positive chemical potentials via a sign-problem-free quantum Monte Carlo simulation [39]. Also, two-dimensional semiconductor systems in the biexciton-dominated regime have been investigated at finite temperature [40].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the theoretical framework of quartet correlations in infinite matter can be applied to other systems such as biexciton condensation [34,35], SU(4) Fermi atomic gases [36][37][38], and charge 4e superconductors [39,40]. In the context of interdisciplinary studies of multicomponent fermions, more than two-body cluster states induced by the Cooper instability [41][42][43][44][45][46][47] and groundstate properties and N -particle off-diagonal long-range order of η pairing in the attractive SU(N ) Hubbard model [48,49] have been studied theoretically.…”
Section: Introductionmentioning
confidence: 99%